Defect Detection of Bolts through Machine Learning ofUltrasonic Testing Signals - Abdul Azziz Abd Talib; Chun Yee Lim; Chin Kian Liew (e-Journal of Nondestructive Testing)
The structural integrity of bolts in civil structures is